ANALISIS RASIO EFEKTIFTAS KEUANGAN PADA DINAS PENDAPATAN DAERAH (DISPENDA) KOTA MAKASSAR - Ester Tamallo (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
The purpose of this study To determine the effectiveness ratio of Finance at the Department of Revenue (Revenue) Makssar city if it is effective. The research method used in this study is